'Honor Among (the Beneficiaries of) Thieves'. - Meketa, Irina (Ethical Theory & Moral Practice, 2015)
Traditional accounts of the fair play principle suggest that, under appropriate conditions, those who benefit from the cooperative labor of others acquire an obligation of repayment. However, these accounts have had little to say about the nature of such obligations within morally or legally problematic cooperative schemes, taking the matter to be either straightforward or unimportant. It is neither. The question of what sorts of fair play obligations obtain for those who benefit from illicit cooperative activity is a matter of great complexity and consequence with implications for, inter alia, global economic justice. In this essay, I explore the nature of this obligation within illicit cooperative schemes, specifically those with so-called negative externalities, or deleterious effects on non-members of the scheme. I conclude that the willing beneficiaries of such schemes acquire a fair-play obligation to recognize and respond to their culpability. This reconceptualization of the fair play principle opens up new avenues for exploring the obligations of those who benefit from acts of collective wrongdoing.